UNDERWOOD ELLIOTT FISHER COMPANY: ADJUSTMENTS BETWEEN EARNED AND CAPITAL SURPLUS; WRITE-OFF OF INTANGIBLE ASSETS. - Fisher, Allan J. (The Accounting Review, 1940)
The article presents accounting case of Underwood Elliott Fisher Co. The enterprise, one of the leading manufacturers of business machines, was incorporated on March 8, 1910, in Delaware under the name of the Underwood Typewriter Co. On December 29, 1927, the name was changed to Underwood Elliott Fisher Co. The corporation manufacturers typewriters and flat-surface accounting and writing machines, including the Elliott Fisher with flat platen and the Underwood and Sundstrand with cylindrical platen. A subsidiary manufactures tally rolls, carbon paper, ribbons and other supplies for the machines of the parent company. The company's products are marketed primarily through branches in the U.S. and through dealers in foreign countries. During the past ten years the surplus accounts of the Underwood Elliott Fisher Co. has undergone two complete cycles involving transfers between earned surplus and capital surplus, arising in the first instance out of the virtual elimination of intangible assets from books of the company.